Urine Angiotensin II Signature Proteins as Markers of Fibrosis in Kidney Transplant Recipients. Issue 6 (June 2019) - Mohammed-Ali, Zahraa; Tokar, Tomas; Batruch, Ihor; Reid, Shelby; Tavares-Brum, Alexandre; Yip, Paul; Cardinal, Héloïse; Hébert, Marie-Josée; Li, Yanhong; Kim, S. Joseph; Jurisica, Igor; John, Rohan; et al.
Abstract : Background: Interstitial fibrosis/tubular atrophy (IFTA) is an important cause of kidney allograft loss; however, noninvasive markers to identify IFTA or guide antifibrotic therapy are lacking. Using angiotensin II (AngII) as the prototypical inducer of IFTA, we previously identified 83 AngII-regulated proteins in vitro. We developed mass spectrometry–based assays for quantification of 6 AngII signature proteins (bone marrow stromal cell antigen 1, glutamine synthetase [GLNA], laminin subunit beta-2, lysophospholipase I, ras homolog family member B, and thrombospondin-I [TSP1]) and hypothesized that their urine excretion will correlate with IFTA in kidney transplant patients. Methods: Urine excretion of 6 AngII-regulated proteins was quantified using selected reaction monitoring and normalized by urine creatinine. Immunohistochemistry was used to assess protein expression of TSP1 and GLNA in kidney biopsies. Results: The urine excretion rates of AngII-regulated proteins were found to be increased in 15 kidney transplant recipients with IFTA compared with 20 matched controls with no IFTA (mean log2 [fmol/µmol of creatinine], bone marrow stromal cell antigen 1: 3.8 versus 3.0, P = 0.03; GLNA: 1.2 versus −0.4, P = 0.03; laminin subunit beta-2: 6.1 versus 5.4, P = 0.06; lysophospholipase I: 2.1 versus 0.6, P = 0.002; ras homolog family member B: 1.2 versus −0.1, P = 0.006; TSP1_GGV: 2.5 versus 1.9; P = 0.15; and TSP1_TIV: 2.0 versus 0.6, P = 0.0006). Receiver operating characteristic curve analysis demonstrated an area under the curve = 0.86 for the ability of urine AngII signature proteins to discriminate IFTA from controls. Urine excretion of AngII signature proteins correlated strongly with chronic IFTA and total inflammation. In a separate cohort of 19 kidney transplant recipients, the urine excretion of these 6 proteins was significantly lower following therapy with AngII inhibitors ( P < 0.05). Conclusions: AngII-regulated proteins may represent markers of IFTA and guide antifibrotic therapies.